Ethnobotany and local conservation of Durio graveolens Becc. (Malvaceae): A threatened wild edible fruit plant in Sumatra, Indonesia - Syamsuardi; Izu Andry Fijridiyanto; Vauzia, Vauzia; Erman Munir; Adi Bejo Suwardi; Kardiman, Reki (Ethnobotany Research and Applications, 2024)
Background: Durio graveolens is essential for the livelihoods of local communities and has been used for multiple purposes. However, the existence of this species is under threat, particularly by human activities. As a result, there is a critical need to conduct ethnobotanical investigations and document indigenous botanical knowledge of local communities in a given area. The aim of the study is to investigate the different ethnobotanical uses of Durio graveolens, as well as the associated indigenous botanical knowledge of the local community, threats, and local conservation practices in Sumatra, Indonesia. Methods: A total of 389 respondents were involved in this study, with gender, age, and educational status considered. Semi-structured interviews and field observations were used to collect data. The data was analyzed using descriptive statistical methods. Pearson’s chi-square test, direct matrix ranking, and pair-wise ranking were used to compute respondents’ ethnobotanical knowledge. Results: Durio graveolens provides multiple uses to local people’s livelihoods as food, building materials, fuelwood, furniture, agricultural tools, fences, and fodder. Local people’s indigenous knowledge of the usage of Durio graveolens has significant correlations with age groups and educational status. Respondents’ consumption habits are significantly related to their age and educational status. Due to agricultural expansion and timber harvest for building materials, the status of Durio graveolens has declined. The attitudes and interests of respondents toward the maintaining and conserving of this species have been found to be significantly related to age groups and educational status. Conclusions: The present study provides information on multiple uses of Durio graveolens. Given the importance of Durio graveolens for people and the environment in improving family food security, as well as the threats to it, it is critical to protect it in natural forests. Concerned studying of this species will eventually allow local people to receive the promised advantages in areas where this plant species is becoming rare, particularly in the Sumatra region. Keywords: Durio graveolens, indigenous knowledge, tropical fruit, West Sumatra Abstrak Latar Belakang: Durio graveolens berperan penting bagi penghidupan masyarakat lokal dan telah digunakan untuk berbagai keperluan. Meskipun demikian, keberadaan spesies ini dalam kondisi terancam, terutama akibat berbagai aktivitas manusia. Oleh karena itu, diperlukan upaya untuk melakukan investigasi etnobotani dan mendokumentasikan pengetahuan botani asli masyarakat lokal di suatu wilayah. Tujuan dari penelitian ini adalah untuk menyelidiki keragaman pemanfaatan Durio graveolens secara etnobotani, serta pengetahuan botani indeginus yang terkait dengan masyarakat lokal, ancaman, dan praktik konservasi lokal di Sumatera, Indonesia. Metode: Sebanyak 389 responden dilibatkan dalam penelitian ini, dengan mempertimbangkan jenis kelamin, usia, dan status pendidikan. Wawancara semi terstruktur dan observasi lapangan digunakan dalam pengumpulan data. Data dianalisis dengan menggunakan metode statistik deskriptif. Uji chi-kuadrat Pearson, pemeringkatan matriks langsung, dan pemeringkatan berpasangan digunakan untuk menghitung pengetahuan etnobotani dari responden. Hasil: Durio graveolens memberikan berbagai manfaat bagi kehidupan masyarakat lokal sebagai bahan pangan, bahan bangunan, kayu bakar, furnitur, alat pertanian, pagar, dan pakan ternak. Pengetahuan masyarakat lokal mengenai pemanfaatan Durio graveolens berkorelasi secara signifikan dengan kelompok umur dan status pendidikan. Kebiasaan konsumsi responden secara signifikan berkaitan dengan umur dan status pendidikan. Akibat perluasan lahan pertanian dan pemanenan kayu untuk bahan bangunan, status Durio graveolens mengalami penurunan. Sikap dan minat responden terhadap pemeliharaan dan konservasi spesies ini berkaitan dengan kelompok umur dan status pendidikan. Kesimpulan: Penelitian ini memberikan informasi tentang berbagai kegunaan Durio graveolens. Mengingat pentingnya Durio graveolens bagi masyarakat dan lingkungan dalam meningkatkan ketahanan pangan keluarga, serta ancaman terhadapnya, maka sangat penting untuk melindungi habitatnya. Kajian yang mendalam terhadap spesies ini pada akhirnya akan memungkinkan masyarakat lokal untuk menerima manfaat pada daerah dimana spesies ini menjadi langka, khususnya di wilayah Sumatera. Kata Kunci: Durio graveolens, pengetahuan asli, buah tropis, Sumatera Barat